Can resin coatings improve the flexural properties of highly viscous glass ionomer cements? - Ong, Joshua Ee Xin; Yap, Adrian U-Jin; Noor Azlin Yahya (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study examined the effect of self-adhesive resin coatings on the flexural properties of three highly viscous glass ionomer cements (HVGICs), specifically Shofu Zirconomer (ZR), GC Equia Forte (EQ), and SDI Riva Self Cure (RV). Custom-made Telfon molds were used to produce 60 beam-shaped specimens (12 × 2 × 2 mm) for each material. The specimens were finished, measured, and randomly divided into three groups of 20. Ten specimens in each group were left uncoated, while the remaining ten were coated with their respective manufacturers’ resin coats. All specimens were immersed in distilled water, artificial saliva or citric acid at 37 °C for seven days and subjected to flexural testing with a 5 KN load at a crosshead speed of 0.5 mm/min till fracture occurred. Flexural data were analysed using one-way ANOVA/Tukey’s post-hoc test and independent sample T-test (α=0.05). Mean flexural modulus ranged from 0.72±0.13 to 13.19±1.00 GPa while mean flexural strength ranged from 4.32±0.84 to 45.83±4.82 MPa after immersing in the different mediums. The flexural modulus/strength of uncoated ZR and RV were generally comparable or greater than when coated. However, EQ was mostly improved when coated regardless of immersion mediums. RV and EQ generally offered the best flexural performance when uncoated and coated respectively.